2009
DOI: 10.1007/s12194-008-0038-x
|View full text |Cite
|
Sign up to set email alerts
|

Use of a clinical MRI scanner for preclinical research on rats

Abstract: This study evaluated the feasibility of imaging rat brains using a human whole-body 3-T magnetic resonance imaging (MRI) scanner with specially developed transmit-and-receive radiofrequency coils. The T(1)- and T(2)-weighted images obtained showed reasonable contrast. Acquired contrast-free time-of-flight magnetic resonance angiography images clearly showed the cortical middle cerebral artery (MCA) branches, and interhemispheric differences could be observed. Dynamic susceptibility contrast MRI at 1.17 mm(3) v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…To assess the brain perfusion of each rat, a region of interest (ROI) was drawn manually along the edge of the brain. To avoid susceptibility artifacts caused by respiratory motion in the trachea (14), the pixels close to the trachea were excluded from ROI selection. The concentration C(t) during the passage of Gd-DTPA could be expressed as:…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To assess the brain perfusion of each rat, a region of interest (ROI) was drawn manually along the edge of the brain. To avoid susceptibility artifacts caused by respiratory motion in the trachea (14), the pixels close to the trachea were excluded from ROI selection. The concentration C(t) during the passage of Gd-DTPA could be expressed as:…”
Section: Discussionmentioning
confidence: 99%
“…To assess the brain perfusion of each rat, a region of interest (ROI) was drawn manually along the edge of the brain. To avoid susceptibility artifacts caused by respiratory motion in the trachea , the pixels close to the trachea were excluded from ROI selection. The concentration C ( t ) during the passage of Gd‐DTPA could be expressed as: CtΔR2*=1normalTElnitalicS()tS0where S ( t ) is the signal intensity in the tissue at time t , S 0 is the average signal intensity during the baseline period and TE is the echo time of the MRI sequence.…”
Section: Methodsmentioning
confidence: 99%
“…MR images were first obtained using a clinical 3 Tesla MRI scanner (Signa HD 3.0 T; GE Healthcare) fitted with an inhouse eight-channel receive-only RF coil (diameter, 50 mm) to assess the whole-body T1-weighted images [22]. After moving the animals to a clinical SPECT system (GCA-7200A; TOSHIBA, Tokyo, Japan) fitted with a low-energy high-resolution (LEHR) parallel-beam collimator, an 123 I-oxLDL sample of 32.5 ± 12.6 MBq with 30 ± 2.5 μg protein/60 μl was injected into the tail vein by bolus (<1.0 s) via a 26-gauge cannula (Safelet-Cath; Nipro, Osaka, Japan).…”
Section: Experiments (B)mentioning
confidence: 99%
“…Using clinical MR systems for this purpose is challenging as clinical scanners have a lower field strength and inferior gradient performance owing to their intended application for human use. Nevertheless, several groups have already demonstrated that clinical systems can be used for small animal imaging (10)(11)(12)(13)(14), including the assessment of the cardiac function of rats and mice (15)(16)(17)(18)(19)(20). Image quality, however, is often limited as a result of breathing and cardiac motion artifacts which may be particularly prominent with Cartesian sampling trajectories.…”
Section: Introductionmentioning
confidence: 99%